2022
DOI: 10.3201/eid2804.220006
|View full text |Cite
|
Sign up to set email alerts
|

Community Transmission of SARS-CoV-2 Omicron Variant, South Korea, 2021

Abstract: et al. Mutation-specific SARS-CoV-2 PCR screen: rapid and accurate detection of variants of concern and the identification of a newly emerging variant with spike L452R mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 6 publications
2
24
0
Order By: Relevance
“…For studies with participants who received booster vaccines, the pooled proportion of asymptomatic infection reached 67.2%, significantly higher than participants who were unvaccinated and received a primary vaccination series, 15,18 urging border vaccination of the third and even the fourth dose of COVID-19 vaccine. However, only slight difference was observed between studies with <65% fully vaccinated individuals and ≥65% fully vaccinated individuals, [20][21][22][23][24][25][26][27][28][29][30] making broad coverage of vaccination seem to be meaningless. This is probably due to decreased pathogenicity of Omicron itself.…”
Section: High Proportion Of Asymptomatic Infection Observed In Childrenmentioning
confidence: 99%
“…For studies with participants who received booster vaccines, the pooled proportion of asymptomatic infection reached 67.2%, significantly higher than participants who were unvaccinated and received a primary vaccination series, 15,18 urging border vaccination of the third and even the fourth dose of COVID-19 vaccine. However, only slight difference was observed between studies with <65% fully vaccinated individuals and ≥65% fully vaccinated individuals, [20][21][22][23][24][25][26][27][28][29][30] making broad coverage of vaccination seem to be meaningless. This is probably due to decreased pathogenicity of Omicron itself.…”
Section: High Proportion Of Asymptomatic Infection Observed In Childrenmentioning
confidence: 99%
“…His main research addresses the quantification and understanding of the mechanisms by which immunization programs affect public health. T he COVID-19 pandemic has severely affected skilled nursing facility (SNF) residents and healthcare personnel (HCP) (1,2). HCP are at high risk for SARS-CoV-2 exposure during patient care (3,4), and were among the earliest groups prioritized for COV-ID-19 vaccination starting in mid-December 2020 (5).…”
Section: About the Authorsmentioning
confidence: 99%
“…S ince its initial detection in November 2021, the SARS-CoV-2 B.1.1.529 (Omicron) variant has become the dominant strain in South Korea. Its emergence led to a large increase in the number of COV-ID-19 cases, mainly through household transmission (1,2). In this study, we sought to estimate the effect of booster vaccinations on reducing the household transmission of COVID-19 to guide current COV-ID-19 mitigation strategy.…”
mentioning
confidence: 99%
“…Multiple previous studies have indicated that asymptomatic or minimally symptomatic SARS-CoV-2 infections are likely triggers of outbreaks as well as ongoing rapid person-to-person transmission across communities. [7][8][9] Although rapid antigen testing kits, which were distributed to facilitate self-diagnosis, are now widely available throughout the US, the extent to which some individuals with Omicron variant infection are unaware of their infection while it is actively transmissible is unknown.…”
Section: Introductionmentioning
confidence: 99%